(3ebGdI GdEScfOQ GdEaQhOjSi aj GdYbd Ydi QCi CQSWhWGdjSs - (3GdGScfOQ GdGaQhOjSjs
(3ChdgG (B:s
(3bGd (B: (3GdYbd YfO CQSWh Ydi KdGKI VQhH s
(3BNQgG (B:s
(3cGf deG UGQ ajfG JeJ GdebGdI hGdMeO ddg cKjQkG s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B14s
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG JdhjK s
(3eUOQ GbJfGA GdCUd (B:s
(3ESchQjGd (B(798 /14) s
Keywords: (3GdadSaI hGdefWbs